Ferro-silicon-manganese-magnesium-titanium-strontium matrix alloy and preparation method thereof
By adding trace elements such as tungsten and gadolinium to the aluminum ferrosilicon manganese magnesium titanium strontium matrix alloy, combining cadmium and niobium, the mechanical and thermal conductivity of the alloy is improved, and the performance problems of existing aluminum alloy materials in high-heat consumption devices and 5G communication base stations are solved, and the application of high-performance materials is realized.
Patent Information
- Application Number
- CN202411805565.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
The existing aluminum alloy materials have shortcomings in thermal conductivity and mechanical properties, especially under the heat dissipation needs of high-heat consumption devices and the high thermal conduction requirements of 5G communication base stations, the performance of traditional metal materials can no longer meet the practical application needs.
Specific alloy preparation methods are used to improve the mechanical and thermal conductivity of the alloy by adding trace amounts of tungsten and gadolinium to the aluminum ferrosilicon manganese magnesium titanium strontium matrix alloy.
It significantly improves the tensile strength, hardness and thermal conductivity of aluminum, ferrosilicon, manganese, magnesium, titanium strontium matrix alloy, and meets the needs of high-performance materials in the fields of high-heat consumption devices and 5G communication base stations.
Smart Images

Figure CN119614962A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy and a preparation method thereof, belonging to the technical field of aluminum alloys. Background Art
[0002] Compared with steel, aluminum alloy has the advantages of high specific strength, high specific stiffness, good thermal conductivity, good corrosion resistance, etc. Compared with titanium alloy and magnesium alloy, it has the advantages of large resource reserves, low cost and good process performance. Therefore, aluminum alloy has become an ideal lightweight material for aerospace industry, communication industry, automobile industry and other industrial fields.
[0003] Different aluminum alloy materials have different thermal conductivity and mechanical properties. At present, the thermal conductivity of ordinary die-cast aluminum alloy is about 90-140W / m·k. In the electronics, electrical, communications, electromechanical and other industries, the working performance is often affected by the heating of components during operation.
[0004] Currently, most of the high thermal conductivity aluminum alloy materials on the market increase their thermal conductivity by doping with rare earth elements, but the strength of the prepared aluminum alloy materials is relatively low.
[0005] Although pure aluminum has a thermal conductivity of up to 237W / m·k, it has poor mechanical properties and casting performance, making it difficult to meet the heat dissipation requirements of high-heat consumption devices in the electronics and communications industries. The thermal conductivity of the high-thermal-conductivity die-cast aluminum alloy (AlSi7-9) currently used in the communications industry is about 170W / m·k, which still cannot meet the heat dissipation performance requirements in certain scenarios. With the popularization of 5G communications, the heat dissipation of base stations is increasing, and the requirements for the thermal conductivity of materials are getting higher and higher. The performance of traditional metal materials can no longer meet the needs of actual applications. Summary of the invention
[0006] The invention provides an aluminum silicon iron manganese magnesium titanium strontium matrix alloy and a preparation method thereof, which improves the mechanical properties and thermal conductivity of the aluminum silicon iron manganese magnesium titanium strontium matrix alloy.
[0007] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0008] The invention discloses an aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy, whose chemical composition by weight percentage is as follows: Si: 8-11%, Fe: 0.6-0.85%, Mn: 0.2-0.6%, Mg: 0.17-0.6%, Ti: 0.1-0.2%, Sr: 0.015-0.04%, W (tungsten) 0.01-0.02%, Gd (gadolinium) 0.03-0.05%, Cu≤0.30%, Pb≤0.02%, Sn≤0.02%, Zn≤0.25%, other single impurities≤0.05, Al: balance.
[0009] The inventors have found that adding trace amounts of tungsten and gadolinium to an alloy based on aluminum silicon iron manganese magnesium titanium strontium can significantly improve the tensile strength, hardness and thermal conductivity of the alloy while promoting alloy refinement, densification and alloying degree.
[0010] The above-mentioned W (tungsten) is added in the form of sodium tungstate.
[0011] The above-mentioned Gd (gadolinium) is added in the form of gadolinium chloride.
[0012] The above-mentioned Si is added in the form of crystalline silicon; iron is added in the form of aluminum-iron 10 alloy; manganese is added in the form of aluminum-manganese 10 alloy; magnesium is added in the form of magnesium ingots; titanium is added in the form of aluminum-titanium 10 alloy; strontium is added in the form of aluminum-strontium 10 alloy.
[0013] In order to further promote the improvement of alloy performance, its chemical composition also includes 0.01-0.02% Cd (cadmium) by weight percentage. The inventors found that the addition of Cd (cadmium) can further promote alloying, reduce burning loss, and promote the improvement of tensile strength and wear resistance.
[0014] The above-mentioned Cd is added in the form of cadmium chloride.
[0015] In order to further promote the improvement of alloy performance, its chemical composition also includes Nb (niobium) 0.01-0.02% by weight.
[0016] The above-mentioned Nb is added in the form of niobium pentoxide.
[0017] A method for preparing an aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy comprises the following steps:
[0018] 1) Evenly spread the measured crystalline silicon on the bottom of a 25-ton tilting aluminum melting furnace;
[0019] 2) After weighing the molten aluminum, the aluminum molten transfer bag is directly filled into a 25-ton tilting aluminum melting furnace. The temperature of the molten aluminum is 700-780℃;
[0020] 3) Raise the temperature to 750-850℃ and start the electromagnetic stirring function, the electromagnetic stirring power is: 0.800HZ, after stirring for 3-5min, add the measured sodium tungstate and gadolinium chloride, stir for 5-8min, then add the measured aluminum manganese 10 alloy, aluminum iron 10 alloy, aluminum titanium 10 alloy, aluminum strontium 10 alloy and magnesium ingot and continue stirring for 50-80min;
[0021] 4) The temperature rises to 820-870℃ and refining begins. The refining time is 10-20min. 1-3 kg of refining agent is added per ton of molten aluminum. The powder spraying refining machine is turned on and the argon pressure is 0.15-0.20Mpa.
[0022] 5) After refining, start slag removal, the slag removal time is ≤25min; after slag removal, let it stand for 10-15min;
[0023] 6) The temperature rises to: 800±50℃, start casting, turn on the online degasser before casting, degasser power: rotor speed: 90-100rmp, argon flow: 40-60L / min, casting time ≤90min.
[0024] After the above casting is completed, the ingot stacking robot stacks the ingots.
[0025] When the raw materials also include cadmium chloride and / or niobium pentoxide, the cadmium chloride and / or niobium pentoxide are added together with sodium tungstate and gadolinium chloride.
[0026] In order to further improve the refining effect, in the above step 4), the refining agent is a mixture of carbon powder and potassium fluoroborate in a mass ratio of 1: (0.5-0.8).
[0027] The above-mentioned refining agent can eliminate the influence of harmful impurities while playing an effective refining and purification effect, ensuring the purification effect of aluminum alloy, and can effectively reduce smoke and irritating odor. While ensuring the strength and quality of the alloy structure, it can effectively reduce the metal loss rate.
[0028] The technologies not mentioned in the present invention are all referred to the prior art.
[0029] The aluminum silicon iron manganese magnesium titanium strontium matrix alloy of the present invention is prepared by adding tungsten, gadolinium and other elements into the aluminum silicon iron manganese magnesium titanium strontium matrix alloy, and the mechanical properties and thermal conductivity of the aluminum silicon iron manganese magnesium titanium strontium matrix alloy are enhanced through the synergistic effect between the elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The internal structure diagram of the aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy obtained in Example 1 (500X);
[0031] Figure 2 The internal structure diagram of the aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy obtained in Example 4 (500X); DETAILED DESCRIPTION
[0032] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0033] Example 1
[0034] Aluminum Silicon Iron Manganese Magnesium Titanium Strontium Tungsten Gadolinium Alloy:
[0035] Raw materials: molten aluminum, crystalline silicon, aluminum-iron 10 alloy, aluminum-manganese 10 alloy, magnesium ingot, aluminum-titanium 10 alloy, aluminum-strontium 10 alloy, sodium tungstate and gadolinium chloride.
[0036] Prepare the raw materials according to the chemical composition by weight percentage: Si: 9.2%, Fe: 0.78%, Mn: 0.38%, Mg: 0.36%, Ti: 0.15%, Sr: 0.033%, W (tungsten) 0.01%, Gd (gadolinium) 0.04% and the balance aluminum.
[0037] The preparation method of the above-mentioned aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy comprises the following steps:
[0038] 1) Evenly spread the measured crystalline silicon on the bottom of a 25-ton tilting aluminum melting furnace;
[0039] 2) The aluminum liquid transfer bag is weighed and then directly filled into a 25-ton tilting aluminum melting furnace. The aluminum liquid temperature is 720°C and the aluminum liquid weight is 20 tons.
[0040] 3) Raise the temperature to 850°C and start the electromagnetic stirring function, the electromagnetic stirring power is 0.800HZ, after stirring for 3 minutes, add the measured sodium tungstate and gadolinium chloride, stir for 5 minutes, then add the measured aluminum manganese 10 alloy, aluminum iron 10 alloy, aluminum titanium 10 alloy, aluminum strontium 10 alloy and magnesium ingot and continue stirring for 60 minutes;
[0041] 4) The temperature rises to 860℃ and refining begins. The refining time is 10min. 1 kg of refining agent (a mixture of carbon powder and potassium fluoroborate with a mass ratio of 1:0.6) is added per ton of aluminum liquid; the powder spraying refining machine is turned on and the argon pressure is 0.15Mpa;
[0042] 5) After refining, start slag removal, the slag removal time is 15 minutes; after slag removal, let it stand for 10 minutes;
[0043] 6) The temperature rises to 800°C and casting begins. Before casting, the online degasser is turned on. The power of the degasser is as follows: rotor speed: 100 rpm, argon flow rate: 50 L / min, and casting time ≤ 90 min.
[0044] 7) Ingot coding robot.
[0045] Product Inspection:
[0046] Element:
[0047]
[0048] When the fracture end face of the product is enlarged 10 times, there is no shrinkage zone, no oxide inclusions, no undissolved metal, the crystals are fine and uniform, and the alloying is good.
[0049] Product density: 2.868g / cm 3; Tensile strength 356MPa; Yield strength 223MPa; Elongation 15%; Hardness 202HBW; Thermal conductivity 206W / m·k; No corrosion was observed in the salt spray test for 168h.
[0050] Comparative Example 1
[0051] The difference from Example 1 is that in step 3), sodium tungstate and gadolinium chloride are omitted. The rest are the same as in Example 1.
[0052] Product density: 2.646g / cm 3 ; Tensile strength 212MPa; Yield strength 92MPa; Elongation 10%; Hardness 154HBW; Thermal conductivity 145W / m·k.
[0053] Comparative Example 2
[0054] The difference from Example 1 is that in step 4), only carbon powder is used as the refining agent. The rest is the same as Example 1.
[0055] Product density: 2.561g / cm 3 ; Tensile strength 330MPa; Yield strength 216MPa; Elongation 14%; Hardness 196HBW; Thermal conductivity 198W / m·k.
[0056] Comparative Example 3
[0057] The difference from Example 1 is that in step 4), only potassium fluoroborate is used as the refining agent. The rest is the same as Example 1.
[0058] Product density: 2.503g / cm 3 ; Tensile strength 316MPa; Yield strength 198MPa; Elongation 12%; Hardness 189HBW; Thermal conductivity 201W / m·k.
[0059] Example 2
[0060] Aluminum Silicon Iron Manganese Magnesium Titanium Strontium Tungsten Gadolinium Cadmium Alloy:
[0061] Raw materials: molten aluminum, crystalline silicon, aluminum-iron 10 alloy, aluminum-manganese 10 alloy, magnesium ingot, aluminum-titanium 10 alloy, aluminum-strontium 10 alloy, sodium tungstate, gadolinium chloride and cadmium chloride.
[0062] Prepare the raw materials according to the chemical composition by weight percentage: Si: 9.2%, Fe: 0.78%, Mn: 0.38%, Mg: 0.36%, Ti: 0.15%, Sr: 0.033%, W (tungsten) 0.01%, Gd (gadolinium) 0.04%, Cd 0.01% and the balance aluminum.
[0063] The preparation method of the above-mentioned aluminum silicon iron manganese magnesium titanium strontium matrix alloy comprises the following steps:
[0064] 1) Evenly spread the measured crystalline silicon on the bottom of a 25-ton tilting aluminum melting furnace;
[0065] 2) The aluminum liquid transfer bag is weighed and then directly filled into a 25-ton tilting aluminum melting furnace. The aluminum liquid temperature is 720°C and the aluminum liquid weight is 20 tons.
[0066] 3) Raise the temperature to 850°C and start the electromagnetic stirring function, the electromagnetic stirring power is 0.800HZ, after stirring for 3 minutes, add the measured sodium tungstate, gadolinium chloride and cadmium chloride, stir for 5 minutes, then add the measured aluminum manganese 10 alloy, aluminum iron 10 alloy, aluminum titanium 10 alloy, aluminum strontium 10 alloy and magnesium ingot and continue stirring for 60 minutes;
[0067] 4) The temperature rises to 860℃ and refining begins. The refining time is 10min. 1 kg of refining agent (a mixture of carbon powder and potassium fluoroborate with a mass ratio of 1:0.6) is added per ton of aluminum liquid; the powder spraying refining machine is turned on and the argon pressure is 0.15Mpa;
[0068] 5) After refining, start slag removal, the slag removal time is 15 minutes; after slag removal, let it stand for 10 minutes;
[0069] 6) The temperature rises to 800°C and casting begins. Before casting, the online degasser is turned on. The power of the degasser is as follows: rotor speed: 100 rpm, argon flow rate: 50 L / min, and casting time ≤ 90 min.
[0070] 7) Ingot coding robot codes ingots.
[0071] Product Inspection:
[0072] Element:
[0073]
[0074] When the fracture end face of the product is enlarged 10 times, there is no shrinkage zone, no oxide inclusions, no undissolved metal, the crystals are fine and uniform, and the alloying is good.
[0075] Product density: 2.912g / cm 3 ; Tensile strength 398MPa; Yield strength 281MPa; Elongation 22%; Hardness 207HBW; Thermal conductivity 212W / m·k; No corrosion was observed in the salt spray test for 168h.
[0076] Example 3
[0077] Aluminum Silicon Iron Manganese Magnesium Titanium Strontium Tungsten Gadolinium Niobium Alloy:
[0078] Raw materials: molten aluminum, crystalline silicon, aluminum-iron 10 alloy, aluminum-manganese 10 alloy, magnesium ingot, aluminum-titanium 10 alloy, aluminum-strontium 10 alloy, sodium tungstate, gadolinium chloride and niobium pentoxide.
[0079] Prepare the raw materials according to the chemical composition by weight percentage: Si: 9.2%, Fe: 0.78%, Mn: 0.38%, Mg: 0.36%, Ti: 0.15%, Sr: 0.033%, W (tungsten) 0.01%, Gd (gadolinium) 0.04%, Nb 0.01% and the balance aluminum.
[0080] The preparation method of the above-mentioned aluminum silicon iron manganese magnesium titanium strontium matrix alloy comprises the following steps:
[0081] 1) Evenly spread the measured crystalline silicon on the bottom of a 25-ton tilting aluminum melting furnace;
[0082] 2) The aluminum liquid transfer bag is weighed and then directly filled into a 25-ton tilting aluminum melting furnace. The aluminum liquid temperature is 720°C and the aluminum liquid weight is 20 tons.
[0083] 3) Raise the temperature to 850°C and start the electromagnetic stirring function, the electromagnetic stirring power is 0.800HZ, stir for 3 minutes, add the measured sodium tungstate, gadolinium chloride and niobium pentoxide, stir for 5 minutes, then add the measured aluminum manganese 10 alloy, aluminum iron 10 alloy, aluminum titanium 10 alloy, aluminum strontium 10 alloy and magnesium ingot and continue stirring for 60 minutes;
[0084] 4) The temperature rises to 860℃ and refining begins. The refining time is 10min. 1 kg of refining agent (a mixture of carbon powder and potassium fluoroborate with a mass ratio of 1:0.6) is added per ton of aluminum liquid; the powder spraying refining machine is turned on and the argon pressure is 0.15Mpa;
[0085] 5) After refining, start slag removal, the slag removal time is 15 minutes; after slag removal, let it stand for 10 minutes;
[0086] 6) The temperature rises to 800°C and casting begins. Before casting, the online degasser is turned on. The power of the degasser is as follows: rotor speed: 100 rpm, argon flow rate: 50 L / min, and casting time ≤ 90 min.
[0087] 7) Ingot coding robot codes ingots.
[0088] Product Inspection:
[0089] Element:
[0090]
[0091] When the fracture end face of the product is enlarged 10 times, there is no shrinkage zone, no oxide inclusions, no undissolved metal, the crystals are fine and uniform, and the alloying is good.
[0092] Product density: 2.935g / cm 3; Tensile strength 406MPa; Yield strength 293MPa; Elongation 25%; Hardness 221HBW; Thermal conductivity 216W / m·k; No corrosion was observed in the salt spray test for 168h.
[0093] Example 4
[0094] Aluminum Silicon Iron Manganese Magnesium Titanium Strontium Tungsten Gadolinium Cadmium Niobium Alloy:
[0095] Raw materials: molten aluminum, crystalline silicon, aluminum-iron 10 alloy, aluminum-manganese 10 alloy, magnesium ingot, aluminum-titanium 10 alloy, aluminum-strontium 10 alloy, sodium tungstate, gadolinium chloride, cadmium chloride and niobium pentoxide.
[0096] Prepare the raw materials according to the chemical composition by weight percentage: Si: 9.2%, Fe: 0.78%, Mn: 0.38%, Mg: 0.36%, Ti: 0.15%, Sr: 0.033%, W (tungsten) 0.01%, Gd (gadolinium) 0.04%, Cd 0.01%, Nb 0.01% and the balance aluminum.
[0097] The preparation method of the above-mentioned aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy comprises the following steps:
[0098] 1) Evenly spread the measured crystalline silicon on the bottom of a 25-ton tilting aluminum melting furnace;
[0099] 2) The aluminum liquid transfer bag is weighed and then directly filled into a 25-ton tilting aluminum melting furnace. The aluminum liquid temperature is 720°C and the aluminum liquid weight is 20 tons.
[0100] 3) Raise the temperature to 850°C and start the electromagnetic stirring function, the electromagnetic stirring power is 0.800HZ, after stirring for 3 minutes, add the measured sodium tungstate, gadolinium chloride, cadmium chloride and niobium pentoxide, stir for 5 minutes, then add the measured aluminum manganese 10 alloy, aluminum iron 10 alloy, aluminum titanium 10 alloy, aluminum strontium 10 alloy and magnesium ingot and continue stirring for 60 minutes;
[0101] 4) The temperature rises to 860℃ and refining begins. The refining time is 10min. 1 kg of refining agent (a mixture of carbon powder and potassium fluoroborate with a mass ratio of 1:0.6) is added per ton of aluminum liquid; the powder spraying refining machine is turned on and the argon pressure is 0.15Mpa;
[0102] 5) After refining, start slag removal, the slag removal time is 15 minutes; after slag removal, let it stand for 10 minutes;
[0103] 6) The temperature rises to 800°C and casting begins. Before casting, the online degasser is turned on. The power of the degasser is as follows: rotor speed: 100 rpm, argon flow rate: 50 L / min, and casting time ≤ 90 min.
[0104] 7) Ingot coding robot codes ingots.
[0105] Product Inspection:
[0106] Element:
[0107]
[0108] When the fracture end face of the product is enlarged 10 times, there is no shrinkage zone, no oxide inclusions, no undissolved metal, the crystals are fine and uniform, and the alloying is good.
[0109] Product density: 3.012g / cm 3 ; Tensile strength 436MPa; Yield strength 332MPa; Elongation 36%; Hardness 236HBW; Thermal conductivity 232W / m·k; No corrosion was observed in the salt spray test for 168h.
Claims
1. An aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy, characterized in that: Its chemical composition by weight percentage is: Si: 8-11%, Fe: 0.6-0.85%, Mn: 0.2-0.6%, Mg: 0.17-0.6%, Ti: 0.1-0.2%, Sr: 0.015-0.04%, W: 0.01-0.02%, Gd: 0.03-0.05%, Cu≤0.30%, Pb≤0.02%, Sn≤0.02%, Zn≤0.25%, other single impurities≤0.05, Al: balance.
2. The ferroalloy of claim 1, characterized in that: W was added in the form of sodium tungstate; Gd was added in the form of gadolinium chloride.
3. The ferroalloy of claim 1 or 2, characterized in that: Si is added in the form of crystalline silicon; iron is added in the form of aluminum-iron-10 alloy; manganese is added in the form of aluminum-manganese-10 alloy; magnesium is added in the form of magnesium ingots; titanium is added in the form of aluminum-titanium-10 alloy; and strontium is added in the form of aluminum-strontium-10 alloy.
4. The ferroalloy of claim 1 or 2, characterized in that: Its chemical composition also includes Cd: 0.01-0.02% by weight.
5. The ferroalloy of claim 4, characterized in that: Cd was added in the form of cadmium chloride.
6. The ferroalloy of claim 1 or 2, characterized in that: Its chemical composition also includes Nb: 0.01-0.02% by weight.
7. The ferroalloy of claim 6, characterized in that: Nb was added in the form of niobium pentoxide.
8. A method for preparing the aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy according to any one of claims 1 to 7, characterized in that: The steps include: 1) Evenly spread the measured crystalline silicon on the bottom of a 25-ton tilting aluminum melting furnace; 2) After weighing the molten aluminum, the aluminum molten transfer bag is directly filled into a 25-ton tilting aluminum melting furnace. The temperature of the molten aluminum is 700-780℃; 3) Raise the temperature to 750-850℃ and start the electromagnetic stirring function, the electromagnetic stirring power is: 0.800HZ, after stirring for 3-5min, add the measured sodium tungstate and gadolinium chloride, stir for 5-8min, then add the measured aluminum manganese 10 alloy, aluminum iron 10 alloy, aluminum titanium 10 alloy, aluminum strontium 10 alloy and magnesium ingot and continue stirring for 50-80min; 4) The temperature rises to 820-870℃ and refining begins. The refining time is 10-20min. 1-3 kg of refining agent is added per ton of molten aluminum. The powder spraying refining machine is turned on and the argon pressure is 0.15-0.20Mpa. 5) After refining, start slag removal, the slag removal time is ≤25min; after slag removal, let it stand for 10-15min; 6) The temperature rises to: 800±50℃, start casting, turn on the online degasser before casting, degasser power: rotor speed: 90-100rmp, argon flow: 40-60L / min, casting time ≤90min.
9. The method for preparing the aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy according to claim 8, characterized in that: Cadmium chloride and / or niobium pentoxide are added together with sodium tungstate and gadolinium chloride.
10. The method for preparing the aluminum-silicon-iron-manganese-magnesium-titanium-strontium matrix alloy according to claim 8 or 9, characterized in that: In step 4), the refining agent is a mixture of carbon powder and potassium fluoroborate in a mass ratio of 1: (0.5-0.8).